Hybrid carbon spherogels: carbon encapsulation of nano-titania. Issue 32 (23rd March 2021) - Salihovic, Miralem; Schoiber, Jürgen; Cherevan, Alexey; Rameshan, Christoph; Fritz-Popovski, Gerhard; Ulbricht, Maike; Arnold, Stefanie; Presser, Volker; Paris, Oskar; Musso, Maurizio; Hüsing, Nicola; Elsaesser, Michael S.
Abstract : Extraordinarily homogeneous, freestanding titania-loaded carbon spherogels can be obtained using Ti(acac)2 (OiPr)2 in the polystyrene sphere templated resorcinol-formaldehyde gelation. Abstract : Extraordinarily homogeneous, freestanding titania-loaded carbon spherogels can be obtained using Ti(acac)2 (OiPr)2 in the polystyrene sphere templated resorcinol-formaldehyde gelation. Thereby, a distinct, crystalline titania layer is achieved inside every hollow sphere building unit. These hybrid carbon spherogels allow capitalizing on carbon's electrical conductivity and the lithium-ion intercalation capacity of titania.